SUMBER PENCEMAR KUALITAS DAN TINGKAT PENCEMARAN AIR DANAU BUYAN DI KECAMATAN SUKASADA KABUPATEN BULELENG BALI - Sumarya, I Made; Ayu Juliasih, Ni Ketut; Sudiartawan, I Putu (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 14 No 2 (2020), 2020)
This research objective examined the source of pollutants, water quality and water pollution level of Buyan Lake. The research conducted field observation to identify the source of pollutants, measuring the water quality and water pollution level of Lake Buyan compared to the standard of environmental quality and damage criteria. This research employed the newest standard measurement and equipment in purpose of water and wastewater inspection. Furthermore, this research used STORET method to analys the pollution level. The results discovered that the pollutant’s source was the settlement and agricultural activities around Buyan Lake. The average value of physical parameters i.e temperature, dissolved residue (TDS), suspended residue (TSS), turbidity and brightness are 23.02 o C; 127 mg.L -1 , 4.71 mg L -1 , 12.52 JTU; and 133.6 cm respectively. The average values ??of the chemical parameters i.e. pH, DO, BOD 5 , COD, NO 3 , NO 2 , Ammonia and Phosphate are 7.48, 5.95 mg.L -1 *, 25.46 mg.L -1 *, 42.99 mg.L -1 *, 1.25 mg.L -1 , 0.054 mg.L -1 , 0.158 mg.L -1 , and 0.149 mg.L -1 respectively. The average values ??of bacteriological parameters i.e Fecal Coliform and Total Coliform are 32.8 MPN/100 ml and 392 MPN/100 ml. The comparation results showed that DO, BOD5, COD, NO 2 , ammonia, phosphate, fecal coliform and total coliform exceed the Class I Standard of Water Quality. STRORET analysis confirmed a high level of pollution i.e. -40. The overall results show that Buyan Lake water is in the heavily polluted category due to domestic and agricultural activities. Keywords : Buyan Lake; Pollutant Sources; Pollution Level and Water Quality.